The Influencing Factors of Somethinc’s Customers’ Purchase Intention in Medan - Wijaya, Jesslyn; Alfonsius (Business Review and Case Studies, 2025)
Background: The beauty industry is one of the most competitive industries locally, contributing significantly to the nation’s economy. With nearly a thousand local beauty brands, there is a huge competitiveness in the industry, with the most popular brands being in the top three. As a newer brand, Somethinc hasn’t been successful in making it to the top 3 local cosmetics brand, which is eventually a necessary goal to thrive in such a competitive industry. Purpose: The research aims to look into how brand trust, E-WoM, self-congruity and perceived quality influence the purchase intention of Somethinc customers in Medan. Design/methodology/approach: The quantitative method is implemented for this research. Data is gathered through accidental sampling with 95 respondents of any gender and age group who are aware of cosmetics and beauty products, analysed through the multiple linear regression test. Findings/Result: The results show that E-WoM, self-congruity and perceived quality have partial significant influence towards the purchase intention of Somethinc customers in Medan, but brand trust has no significant partial influence. Conclusion: Brand trust does not have a partial significant influence on the purchase intention of Somethinc’s customers in Medan, E-WoM has a partial significant influence on the purchase intention of Somethinc’s customers in Medan, self-congruity has a partial significant influence on the purchase intention of Somethinc’s customers in Medan, and perceived quality has a partial significant influence on the purchase intention of Somethinc’s customers in Medan, with perceived quality contributing the most influence to purchase intention.. Originality/value (State of the art): The originality of this research is that it also discusses how brand trust can have no influence on purchase intention, with the context of a newly established brand not having built enough brand trust yet. Keywords: brand trust, E-WoM, perceived quality, purchase intention, self-congruity